Método de evaluación en el área de educación física en los niños y niñas de educación básica de la Unidad Educativa Pucayacu en el periodo lectivo 2016 - 2017 - Beltrán López, Juan Carlos (2018)
Physical Education has been used by man, as means of expression, fun, and occupation of his time. The present work aims to improve the use and empathy for the Physical Education class for decades they have been evaluated in a routine, way unconventional way without knowing the different physical and intellectual abilities of the students, and they have been applied activities that demand physical strength in its highest evaluative percentage, decreasing the ability to improve the use of students of low physical strength. Through a series of inductive-deductive methods, type of field research, descriptive methodology, qualitative, field research study, it was concluded that one of the needs of this community is the application of a more specific evaluation method so that the work was projected as a proposal, the elaboration of an evaluation method with parameters according to the area of Physical Education, this allowed the improvement of the use, empathy and integral development within the area of Physical Education. The social impact that this project presented and its execution was positively causing great changes optimizing the social, academic, and psychological problems of the students.